1983
DOI: 10.1007/bf00379558
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation and turnover of stable carbon isotopes in animal tissues: Implications for ?13C analysis of diet

Abstract: The use of stable carbon isotopes as a means of studying energy flow is increasing in ecology and paleoecology. However, secondary fractionation and turnover of stable isotopes in animals are poorly understood processes. This study shows that tissues of the gerbil (Meriones unguienlatus) have different δC values when equilibrated on corn (C) or wheat (C) diets with constant C/C contents. Lipids were depleted 3.0‰ and hair was enriched 1.0‰ relative to the C diet. Tissue δC values were ranked hair>brain>muscle>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

48
1,388
5
50

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,577 publications
(1,491 citation statements)
references
References 26 publications
48
1,388
5
50
Order By: Relevance
“…Red blood cells and muscle were the tissues chosen for comparative analyses among the different species because these tissues integrated diet over relatively long periods (≥ 2 to 3 mo: Tieszen et al 1983, Hobson & Clark 1992b, Hilderbrand et al 1996.…”
Section: Study Area -Estuary and Gulf Of St Lawrencementioning
confidence: 99%
See 2 more Smart Citations
“…Red blood cells and muscle were the tissues chosen for comparative analyses among the different species because these tissues integrated diet over relatively long periods (≥ 2 to 3 mo: Tieszen et al 1983, Hobson & Clark 1992b, Hilderbrand et al 1996.…”
Section: Study Area -Estuary and Gulf Of St Lawrencementioning
confidence: 99%
“…when δ 13 C values were corrected using a 1.3 ‰ 13 C-enrichment per trophic level ( Table 2). The δ 13 C value of Estuary harp seals suggests that they had been in the Estuary since at least early December, assuming a half-life of 4 wk for muscle tissue and a spread over 2 to 3 mo in δ 13 C changes (Tieszen et al 1983). This coincides with the seasonal timing of observations of large numbers of harp seals in the Lower Estuary (Sergeant 1991).…”
Section: Patterns Of 13 C Signatures and Trophic Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that the degree of this alteration depends on the component or body tissue considered, due to its biochemical composition and turnover rate. 22 On the other hand, variations in the SIRs in milk and milk derivatives following suitable experimental design have not been so extensively explored. Metges et al 23 investigated the 13 C/ 12 C of CO 2 breath, bulk milk and serum by exchanging a C 3 plant with a C 4 plant diet, and vice versa.…”
mentioning
confidence: 99%
“…Stable isotope ratios of nitrogen ( 15 N/ 14 N, expressed as d 15 N) and carbon ( 13 C/ 12 C, expressed as d 13 C) in consumer tissues have been used to determine trophic relationships within food webs and whether a food chain or food web is based on C 3 plants (d 13 C & -23% to -32%), C 4 plants (d 13 C & -16% to -9%), or a mixture of the two groups (De Niro and Epstein 1978;Tieszen et al 1983). Similarly, stable isotopes of hydrogen in bird feathers (dD f ) have been positively correlated with stable isotopes of hydrogen in rain (dD p ; Chamberlain et al 1997;Hobson and Wassenaar 1997).…”
mentioning
confidence: 99%